Supramolecular Self-Assembled Nanospheres for Enzyme Encapsulation Based on Cyclodextrin - Zhenqiang Dong; Lili Wu; Dongdong Ma (Journal of Chemistry)
Based on the cyclodextrin (CD) and guest molecules inclusion, a novel rigid-flexible polymeric nanosphere was prepared by supramolecular self-assemble. The rigid part was formed by α-cyclodextrin (α-CD) and methoxypolyethylene glycol (mPEG) necklace-like crystallites while the flexible part was sodium alginate (Alg). The rigid and flexible parts were linked by β-cyclodextrin (β-CD) and ferrocene (Fc) inclusion complex. This kind of nanosphere exhibited good glucose oxidase (GOD) encapsulation ability. The encapsulated enzyme, in comparison to the free enzyme, is able to retain its high activities across a rather broader range of pH, temperature, and time. After 20 days, the encapsulated enzyme can retain its almost 86% initial activity which exhibited good storage stability. These studies suggested that CD host-guest inclusions to form stable polymeric nanospheres may be an effective way for enzyme encapsulation in various biomedical applications.